Comparison of intubating conditions in two different head elevations for direct laryngoscopy in stretcher – A prospective randomized controlled study - Tejasri Ketireddy; Kavitha Jayaram; Singam Geetha; Archana Pathy; Padmaja Durga (The Indian Anaesthetists' Forum)
Background and Aims: Sniffing position for laryngoscopy is considered the gold standard for better glottic visualization. However, there are no studies regarding ideal positioning of head and neck for patients intubated in stretcher either in the operating room or in the emergency area. The aim of the study was to compare the glottic visualization and intubating conditions during direct laryngoscopy using conventional head cushion or Popitz Pillow for patients intubated in stretcher. Methods: This prospective randomized controlled study was conducted on patients with the age of 18 and 60 years, of any gender undergoing elective spine surgery in prone position. Study participants were divided into two groups (Group S – Conventional head cushion, Group P – Popitz Pillow). After induction of anesthesia in stretcher, they were positioned for direct laryngoscopy with either of the pillows as per the group. Preoperative airway parameters, intubation difficulty score (IDS), time taken for intubation were measured. Results: Hundred and fifty-six patients enrolled for the study were randomized into two groups. Almost 82.1% of the patients in Group P had Cormack–Lehane grading 1 when compared to 53.8% in Group S. Time taken for intubation was statistically significant between the two groups with P = 0.0001. In Group P, 64 (82.1%) patients had easy IDS, whereas only 43 (55.1%) patients had easy IDS in Group S. Conclusion: Popitz Pillow provided better intubating conditions, improved laryngeal view in patients intubated on stretcher for prone position surgeries when compared to conventional head cushion.